Sketsa Pelayanan Gereja Sebelum, Selama, dan Sesudah Masa Pandemi COVID-19 - Teng, Michael; Margaret, Carmia (Sekolah Tinggi Teologi SAAT, 2020)
Sketches of Church Ministry Before, During, and After the COVID-19 Pandemic. The COVID-19 pandemic can be likened to a â€œmirrorâ€ that shows the authenticity of church ministriesâ€™ real faces. Before the pandemic, there had been observations emerging from various kinds of literature, research, and various experiences in the ministry context that showed a separation between biblical theology and the ministryâ€™s praxis and the neglect of the primary things in the ministry. These two observations seem to be proven to be true during the pandemic. In three studies on church services conducted in Indonesia during the pandemic, namely a series of researches from Bilangan Research Center, National Survey and National Dialogue from South East Asia Bible Seminary, Malang, as well as a series of researches from the Center for the Church Growth Studies of Amanat Agung Theological School, Jakarta, it was found that the church still has a disproportionate concept of theodicy. The church services are still very dependent on the clergyâ€™s role as professionals and narrowly centered merely on the worship ministry. There is also a serious gap between the older and the younger generation, and church services are not yet ready to deal with technology. Responding to this reality, the writers propose that the church needs to refocus its post-pandemic ministry in six ways, namely: building a theological vision that can be embodied in the ministry, making worship ministry a central but not as a center in ministry, developing family-based discipleship, strengthening pastoral ministry that emphasizes deep personal relationships, paying attention to ministering the next generation, and prioritize the sending capacity rather than solely the seating capacity.